The Environmental footprint of morphine: a life cycle assessment from opium poppy farming to the packaged drug. Issue 10 (21st October 2016) - McAlister, Scott; Ou, Yanjun; Neff, Elise; Hapgood, Karen; Story, David; Mealey, Philip; McGain, Forbes
Abstract : Objective: To examine the environmental life cycle from poppy farming through to production of 100 mg in 100 mL of intravenous morphine (standard infusion bag). Design: 'Cradle-to-grave' process-based life cycle assessment (observational). Settings: Australian opium poppy farms, and facilities for pelletising, manufacturing morphine, and sterilising and packaging bags of morphine. Main outcome measures: The environmental effects (eg, CO2 equivalent ('CO2 e') emissions and water use) of producing 100 mg of morphine. All aspects of morphine production from poppy farming, pelletising, bulk morphine manufacture through to final formulation. Industry-sourced and inventory-sourced databases were used for most inputs. Results: Morphine sulfate (100 mg in 100 mL) had a climate change effect of 204 g CO2 e (95% CI 189 to 280 g CO2 e), approximating the CO2 e emissions of driving an average car 1 km. Water use was 7.8 L (95% CI 6.7– to 9.0 L), primarily stemming from farming (6.7 L). All other environmental effects were minor and several orders of magnitude less than CO2 e emissions and water use. Almost 90% of CO2 e emissions occurred during the final stages of 100 mg of morphine manufacture. Morphine's packaging contributed 95 g CO2 e, which accounted for 46% of the total CO2 e (95% CI 82 to 155 g CO2 e). Mixing, filling and sterilisation of 100 mg morphine bags added a further 86 g CO2 e, which accounted for 42% (95% CI 80 to 92 g CO2 e). Poppy farming (6 g CO2 e, 3%), pelletising and manufacturing (18 g CO2 e, 9%) made smaller contributions to CO2 emissions. Conclusions: The environmental effects of growing opium poppies and manufacturing bulk morphine were small. The final stages of morphine production, particularly sterilisation and packaging, contributed to almost 90% of morphine's carbon footprint. Focused measures to improve the energy efficiency and sources for drug sterilisation and packaging could be explored as these are relevant to all drugs . Comparisons of the environmental effects of the production of other drugs and between oral and intravenous preparations are required.